Eurozone stock market reaction to monetary policy interventions and other covariates - Nikolaos Petrakis; Christos Lemonakis; Christos Floros; Constantin Zopounidis (Journal of Risk and Financial Management, 2022)
The joint effect of the global economic and sovereign debt crisis forced the European Central Bank (ECB) to apply conventional and non-standard expansionary monetary policy interventions in order to stabilize eurozone economies. We conducted a panel regression econometric analysis to study the influence of euro area monetary authority policy interventions, along with two main macroeconomic variables and a sentiment indicator, on market equity returns of eurozone countries for the period January 2007 to December 2017. Our findings suggest that conventional and non-standard monetary policy innovations had a positive lagged impact on equity returns of euro area monetary markets. More specifically, interest rate cuts evenly influenced market indices while non-conventional actions mainly affected core eurozone countries that were less affected by the crisis. We also document a strong negative relationship between inflation rates and market returns. In addition, the sentiment indicator produces positive effects on returns because it contains information that is not incorporated into other macro variables.
Keywords: 330; monetary policy; Central Bank; financial crisis; panel data